METAPHORICAL EXPRESSIONS OF SADNESS IN ENGLISH AND JAPANESE - Irma; Yusrita Yanti; M. Aziz (Jurnal Kata, 2021)
There are various words used to express basic emotions, such as Anger, Sadness, Joy, and Fear both literally and figuratively. This study focused on metaphorical expressions, one of the figurative expressions to convey Sadness in English and Japanese. Every culture has a different concept in expressing emotions metaphorically. So, this paper describes how English and Japanese express their Sadness through metaphor, and how they think Sadness is an analogy or a comparison to something else. Data were taken from the sadness metaphor listed by Kövecses (2000), Esenova (2011) English and Japanese song lyrics. A qualitative method was used in analyzing the data in a framework of semantics theories. The results show that English and Japanese have similarities and differences. The similarities can be contributed to the universality of conceptual metaphors and the differences can be related to particular culture modes in English and Japanese.